Hexanchorus bifurcatus sp. nov., a new tepui riffle beetle (Coleoptera: Elmidae: Larainae) from Tafelberg, Suriname - Maier, Crystal A.; Short, Andrew Edward Z. (Zootaxa, 2014)
Here we present the first published record of a laraine elmid from Suriname, which represents a new species – Hexanchorus bifurcatus sp. nov. Specimens were collected from the summit of Tafelberg, a table mountain near the Wilhelmina Range of Suriname. This species can be distinguished from all other Hexanchorus by the bifurcate elytral apices and median projection of the third abdominal ventrite of the female, as well as the distinctive male genitalia. Habitus photos, illustrations of the genitalia, a distribution map, notes on habitat, and comparative diagnoses are provided.